Absence of radiative corrections in four-dimensional topological Yang-Mills theories - Junqueira, Octavio; Duarte Pereira Junior, Antônio; Sadovski, G.; Sobreiro, R. F.; Tomaz, A. A. (Physical review, 2018)
We prove that all connected n-point Green functions of four-dimensional topological Yang-Mills theories quantized in the (anti-)self-dual Landau gauges are tree-level exact, i.e., there are no radiative corrections in this gauge choice.